PSO-based specified structure mixed H2/H∞ multiple PHEV controllers for robust frequency control in interconnected power systems with large wind farms - Rattanapornchai, Chalotorn; Ngamroo, Issarachai (My University, 2013)
This paper focuses on the new robust control design of multiple plug-in hybrid electric vehicle (PHEV) units for frequency control in interconnected power systems with large wind farms. The controller structure of PHEV is specified as a proportional integral (PI). Unstructured system uncertainties such as various wind patterns, system parameters variation, are modeled by the inverse output multiplicative perturbation. The particle swarm optimization is applied for tuning the PI parameters for all PHEV units based on the mixed H2/H∞ control approach. Simulation results confirm the superior performance and robustness of the proposed PHEV controller. © 2013 ISSN 1881-803X.
Keywords: Frequency control; Mixed H2/H∞ control; Particle swarm optimization; Plug-in hybrid electric vehicle; System uncertainties